MicroRNA-155 Promotes Heat Stress-Induced Inflammation via Targeting Liver X Receptor α in Microglia - Li, Ping; Wang, Gong; Zhang, Xiao-Liang; He, Gen-Lin; Luo, Xue; Yang, Ju; Luo, Zhen; Shen, Ting-Ting; Yang, Xue-Sen (Frontiers in Cellular Neuroscience, 2019)
Background: The neuroinflammatory responses of microglial cells play an important role in the process of brain dysfunction caused by heat stroke. MicroRNAs are reportedly involved in a complex signaling network and have been identified as neuroinflammatory regulators. In this study, we determined the biological roles of microRNA-155 in the inflammatory responses in heat-stressed microglia and explored the underlying mechanisms. Methods: MicroRNA-155 mimic and inhibitor were used to separately upregulate or downregulate microRNA-155 expression. The activation state of BV-2 microglial cells (BV-2 cells) was assessed via immunoreactions using the microglial marker CD11b and CD68. Levels of induced interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were measured using real-time reverse transcription polymerase chain reaction (RT-PCR) and enzyme linked immunosorbent assays (ELISAs). The activation of nuclear factor kappa B (NF-κB) signaling proteins was evaluated by Western blotting for inhibitory kappa B alpha (IκBα) and NF-κB p65 phosphorylation and indirect immunofluorescence analysis using a p65 phosphorylation antibody. A luciferase reporter assay was used to verify liver X receptor α (LXRα) as a target gene of microRNA-155. Results: Heat stress significantly induced IL-1β, IL-6, and TNF-α release and increased the expression of CD11b and CD68. In addition, IκBα and NF-κB p65 phosphorylation were dramatically increased by heat stress, and microRNA-155 expression was also elevated. High expression of microRNA-155 in heat-stressed microglial cells was inversely correlated with LXRα expression. We then determined the role of microRNA-155 in the heat stress-induced inflammatory responses. The results revealed that by targeting LXRα, microRNA-155 enhanced NF-κB signaling activation and facilitated immune inflammation in heat stress-treated BV-2 cells. Conclusion: MicroRNA-155 promotes heat stress-induced inflammatory responses in microglia. The underlying mechanisms may include facilitating inflammatory factors expression by increasing NF-κB pathway activation via targeting LXRα.